Interpretacje Carla Schmitta na świecie i w Polsce - Wielomski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The purpose of this text is the comparison of the interpretations of Carl Schmitt’s thought in Poland and worldwide. Polish literature on Schmitt is very modest: two large monographs and some scientific articles. It focuses on the problem of the theory of the state and politics. At the same time, the world literature is very abundant. Schmitt is a thinker concerned with many topics. He wrote about many problems. For a long time there has been a tendency to look for the interpretive key to use in order to find a central theme of his reflections and then read the rest of his works through this perspective. Researchers identify these central themes as: a critique of liberalism, political theology, favorability towards Nazism, political opportunism. This text shows four major worldwide interpretations and their reflection in the Polish-language literature.
Keywords: Schmitt, Carl; myśl polityczna; interpretacja; Polska; świat